ALAT PELAPIS LOGAM ELECTROPATING HASIL PENELITIAN UNTUK PRAKTIK SISWA SMK - Riswan Dwi Jatmiko, Soeprapto Rachmad Said, Heri Wibowo, (Universitas Negeri Yogyakarta, 2014)
The purpose of this PPM Featured is (1) determining the shape ofelectroplating tools that fit with the needs of Vocational High School Diponegorowith low operating costs; (2) students and teachers can operate theelectroplating tool and metal plating with the correct procedures; (3) determiningthe response of the students and teacher after practicing the metalplating and the Vocational High School Diponegoro has its own electroplatingtool.The method used in the PPM Featured electroplating are planningthe tool with the size as needed in Vocational High School Diponegoro,easily portable, safe, minimal pollution, and easy to use. To prevent failurein the PPM implementation, then all sizes and components used in the electroplatingtool together with the size and components used in the electroplatingtool based on research results. Testing and training the students andteachers about the tool and operation of the metal plating appliance.The implementation of PPM Featured produce something as follows:(1) the construction shape of electroplating tool were rectangular a longframe size of 1000 mm , 400 mm width and 750 mm height. Electroplatingbath size were 560 mm length, 300 mm width and 400 mm height. Nickelsolution volume was 55 liters. The framework equipped with troll in orderto be easily moved and also equipped with table, (2) 73 students had themean value > 78 and 1 teacher can operate and utilize the electroplatingtools for metal plating (iron/steel), (3) the responses of the students andteacher after practice with electroplating tools were expressed great satisfaction.Keywords: electroplating tools, plating, operation, and students